Software Developers’ Perceptions of Productivity: An Industry-focused Study - Coelho, Murilo; Reinbold, Isabelle; Sancho, Lizie; Paixao, Matheus; Araújo, Allysson Allex; Freire, Sávio (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2025.13759, 2025)
Context: Developer productivity is a critical factor of software project success and, by extension, a key driver of organizational performance and software quality in software engineering. In the era of Generative Artificial Intelligence (GenAI), understanding the developers’ perception of productivity becomes paramount for a software organization seeking to adopt GenAI tools. Objective: This paper aims to examine developers’ perception of productivity, focusing on its measurement and the expected impact of adopting GenAI. Method: We conducted two semi-structured focus groups with software developers from a large science and technology institute. We also administered a confirmatory questionnaire to support the verification of our findings. The collected data were analyzed using content analysis. Results:We identified five key productivity factors: quality, expectations, deadlines, progress, and efficiency, including distinct measurement systems for coding, code review, and documentation activities. Participants consistently emphasized the potential of GenAI to streamline and enhance a range of routine development tasks, albeit with certain limitations regarding their use. Conclusion: Our findings indicate that productivity constitutes a complex multidimensional construct influenced by interrelated factors. Moreover, GenAI emerge as a transformative technology whose impacts on productivity require deeper investigation in future studies, particularly regarding balancing efficiency gains with the preservation of technical abilities.